Ocupação como Determinante de Saúde: uma análise centrada no estudante e no contexto universitário - Rodrigues, Daniela da Silva (2022)
Studies have pointed to an emerging demand for psychosocial problems in the university environment, such as common mental disorders (CMD), which can be generated by a change in educational environment – from high school to higher education. Research also shows that entering university is a critical phase of students’ lives, as it requires an occupational and social adaptation to respond to institutional and rules requirements. When performance the role of student, many internal (personal) and external (environmental) factors may interfere with competence and occupational participation, in order to provide satisfaction and promote health or trigger suffering. In this sense, occupation, as a contextualized action, becomes a determining element of health. The aim was to identify the relation between health (CMD and quality of life) and occupation (competence and occupational interest) of university students, in the areas of health and exact, of a Brazilian public university, in the context of pandemic of Covid-19. This is a cross-sectional and correlation study, conducted from May to September 2020, with a sample of 493 students, who answered an electronic questionnaire on sociodemographic variables, the Occupational Self Assessment (OSA) Brazil and the Self Reporting Questionnaire - 20 (SRQ - 20). Descriptive, bivariate and logistic regression analyses were performed using the Statiscal Package for Social Science (SPSS), version 21.0. The results showed that the prevalence of CMD among students was 66.1%, with predictors related to being female (p<0.001) and being from some exact science course (p=0.050). The students judged their quality of life good (54%) and were dissatisfied with their own health (35.5%). Regression analysis showed significantly negative associations for CMD (p<0.001) and postive associations for occupational competence (p<0.001), with all domains of quality of life. Occupational competence presented as significantly negative predictors the semester of the course (p=0.005) and the presence of CMD (p<0.001). The occupational interest scale presented the semester of the course as a significantly positive predictor (p=0.005). This study showed that being in psychological distress may affect the quality of life and occupational competence of university students, reflecting on the performance of daily occupations. Therefore, it is important to outline proposals for prevention and promotion actions focused on student care. Above all, promote support service policies that effectively discuss sustainable support networks and create strategies for mental health care that integrate health, social and occupational determinants, prioritizing student life and the academic community.